2016
DOI: 10.1007/s10543-016-0616-y
|View full text |Cite
|
Sign up to set email alerts
|

Radial basis function partition of unity operator splitting method for pricing multi-asset American options

Abstract: PostprintThis is the accepted version of a paper published in BIT Numerical Mathematics. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination. AbstractThe operator splitting method in combination with finite differences has been shown to be an efficient approach for pricing American options numerically. Here, the operator splitting formulation is extended to the radial basis function partition of unity method. An approach that has previously often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In [43], Peherstorfer et al suggested reduced models for pricing basket options with the Black-Scholes and the Heston models. Shcherbakov [48] extended the operator splitting formulation to the radial basis function partition of unity method. A FEM in spatial variables and alternating direction implicit (ADI) method based on the semi-implicit approximation in time variable has been studied in [34].…”
Section: Introductionmentioning
confidence: 99%
“…In [43], Peherstorfer et al suggested reduced models for pricing basket options with the Black-Scholes and the Heston models. Shcherbakov [48] extended the operator splitting formulation to the radial basis function partition of unity method. A FEM in spatial variables and alternating direction implicit (ADI) method based on the semi-implicit approximation in time variable has been studied in [34].…”
Section: Introductionmentioning
confidence: 99%
“…In later years, RBFs method has attracted a large number of researchers and practitioners to solve many practical problems [2–14]. RBFs based methods have also been numerically tested for solution of Black–Scholes model and its variants [4, 15–17]. As a truly meshless method, it works for arbitrarily provided data points for initialization and equally effective in higher dimensions due to straight‐forward formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Both of those pricing problems can be formulated as time-dependent multidimensional partial differential equations (PDEs). As a high-order, mesh-free and sparse numerical method from the RBF family, together with the Radial Basis Function Partition of Unity (RBF-PU) method [35,36,33], RBF-FD shows strong potential when it comes to solving multidimensional PDEs. We develop on top of the previous results of using RBF-FD for financial engineering [31,14,24,27,23,22], and use important recent advancement of the RBF-FD approximation in other disciplines [1,8], to build stable, accurate, and fast solvers for multidimensional PDEs in finance.…”
Section: Introductionmentioning
confidence: 99%